Analysis of Needs for the Development of Islamic Cultural History Teaching Materials Based on Independence Learning at Fatmawati Sukarno State Islamic University Bengkulu - Maryam, Maryam; Rohimin, Rohimin; Amin, Alfauzan; Rizal, Syamsul; Bety, Bety (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2024)
This article aims to analyze the needs to develop history of Islamic culture teaching materials in Madrasah Ibtidaiyah Teacher Education (PGMI) study program based on learning independence. The research was carried out using descriptive and qualitative methods. Data was collected through the distribution of questionnaires and in-depth interviews with lecturers and students, and analyzed using interactive models. Based on the research conducted, it was found that the teaching materials used in Islamic History and Culture Madrasah Ibtidaiyah lectures were teaching materials that were not written by lecturers and were considered unable to increase student interest, motivation, and independence in learning. Both lecturers and students agree to develop teaching materials related to learning independence. In addition, the teaching materials to be developed are expected to focus on the material in the curriculum, which covers four main topics: 1) The condition of Arab society before Islam; 2) History of Prophet Muhammad, Da'wah, and personality of Prophet Muhammad (peace be upon him); 3) The event of the Prophet Muhammad's Hijra to Medina and the event of Fathul Mecca; 4) Civilization at the time of Khulafausrrasyidin. Another result of this study is that the Islamic History and Culture Madrasah Ibtidaiyah teaching materials to be developed should refer to the principles of teaching material development, especially teaching materials with instructions for use and materials that follow the lecture syllabus.